Effects of hydrothermal carbonization temperature on carbon retention, stability, and properties of animal manure-derived hydrochar - Li, Feiyue; Jiang, Zelun; Ji, Wenchao; Chen, Yihan; Ma, Jiran; Gui, Xiangyang; Zhao, Jianrong; Zhou, Chunhuo (International Journal of Agricultural and Biological Engineering, 2022)
Hydrothermal carbonization of animal manure is being increasingly recognized as a green process for hydrochar production. Temperature obviously affects the properties of hydrochar especially with respect to carbon retention and stability. These properties determine the carbon sequestration potential of hydrochar but related researches are limited. In this study, chicken, dairy, and swine manures were collected and hydrothermal carbonized under different temperature conditions, aiming to study the fuel characteristics, carbon retention, and stability of hydrochar influenced by temperature. Results show that high temperature led to low yield and declined H/C, O/C, and volatile matter of hydrochar. While high temperature caused high fixed carbon, fuel ratio, and heating value of hydrochar, indicating that animal manure hydrochar can be adopted as an alternative of fuel. After hydrothermal carbonization, less than half of carbon from animal manure was retained in hydrochar: 22.70%-46.71% for chicken manure, 39.36%-49.72% for dairy manure, and 36.24%-64.21% for swine manure. The carbon retention decreased with the increase of temperature. Conversely, high temperature improved the aromatic and strengthened the resistance to thermal oxidation of hydrochar, which was evidenced by FTIR and TGA analysis. Moreover, the carbon sequestration capacity of animal manure hydrochar was less than a third of total carbon (originated from animal manure) and relatively low temperature (no more than 250°C) was beneficial to produce hydrochar for carbon sequestration.Keywords: livestock manure, carbon sequestration, hydrochar, hydrothermal temperatureDOI: 10.25165/j.ijabe.20221501.6758Citation: Li F Y, Jiang Z L, Ji W C, Chen Y H, Ma J R, Gui X Y, et al. Effects of hydrothermal carbonization temperature on carbon retention, stability, and properties of animal manure-derived hydrochar. Int J Agric & Biol Eng, 2022; 15(1): 124–131.